Unfulfilled Promise?: Prevalence and determinant factors of child anemia during the COVID-19 Pandemic in Peru - Salazar Zapata, Pamela (2024)
Anemia is a global public health issue exacerbated by economic, social, and cultural inequalities. This disorder increases childhood morbidity and mortality, adversely affecting short- and long-term health and quality of life. This study aims to identify determinants of anemia among children aged 6 to 59 months in Peru, segmented across pre-pandemic, pandemic, and post-pandemic periods. Logistic and normal models are employed using data from the National Demographic Health Survey (ENDES) 2018-2023. Findings indicate that maternal anemia, fever, and diarrhea increase the likelihood of childhood anemia prevalence during all three study periods.